Den supplementation for black bears in coastal British Columbia. (10th October 2022) - Davis, Helen
Abstract: American black bears ( Ursus americanus ) require suitable den sites that provide security and cover to successfully survive the winter denning period. On Vancouver Island, British Columbia, Canada, black bears prefer to use cavities associated with large‐diameter hollow trees or structures derived from trees (i.e., cavities in or under logs, root boles and stumps) as den sites. Extensive harvesting of coastal forests has reduced the availability of natural den structures such that their supply may affect population sustainability. I attempted to develop new methods to address the declining supply of denning opportunities by creating and testing new den structures constructed in trees, stumps and from plastic. Between 2014–2021, I created or deployed and monitored 17 potential den structures in 2 study areas that were believed to have low den supply. I documented up to 51 visits by bears at each structure; every one of the video‐monitored structures was investigated at least 5 times. None of the plastic artificial den structures were used by bears, but an enhanced natural structure was used as a den over 4 consecutive winters. My work indicates that bears will find and investigate all natural or artificial denning structures in their environment, but artificial structures do not appear to be a viable method to mitigate losses of dens caused by forest harvesting. Abstract : Attempts were made to create dens for black bears in an area with extensive forest harvesting that removed dens in hollow trees. Bears utilized an augmented old growth stump as a den but did not utilize artificial dens made of plastic.